2022
DOI: 10.1101/2022.02.14.480318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting vertical ground reaction forces from 3D accelerometry using reservoir computers leads to accurate gait event detection

Abstract: Accelerometers are low-cost measurement devices that can readily be used outside the lab. However, determining isolated gait events from accelerometer signals, especially foot-off events during running, is an open problem. We outline a two-step approach where machine learning serves to predict vertical ground reaction forces from accelerometer signals, followed by force-based event detection. We collected shank accelerometer signals and ground reaction forces from five adults during comfortable walking and run… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Our Waist model aligns with other groups that have used machine learning or regression equations to estimate vGRF loading peak during walking or running [ 22 , 23 ]. Although lower leg sensor sites can accurately estimate vGRF signals under different scenarios [ 24 , 25 ], we found that accelerometers placed near the body’s center of mass may provide optimal features to estimate vGRF during walking. This outcome is theoretically supported by simple Newtonian physics-based models of walking [ 21 ], in that acceleration of the body’s center of mass is proportional to the net external force acting on the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our Waist model aligns with other groups that have used machine learning or regression equations to estimate vGRF loading peak during walking or running [ 22 , 23 ]. Although lower leg sensor sites can accurately estimate vGRF signals under different scenarios [ 24 , 25 ], we found that accelerometers placed near the body’s center of mass may provide optimal features to estimate vGRF during walking. This outcome is theoretically supported by simple Newtonian physics-based models of walking [ 21 ], in that acceleration of the body’s center of mass is proportional to the net external force acting on the body.…”
Section: Discussionmentioning
confidence: 99%
“…However, those authors did not include comparisons to a waist- or hip-worn sensor [ 24 ]. Bach et al (2022) used only shank accelerometers to estimate vGRF profiles with R 2 = 0.97 and a normalized root mean square error of 5.2% [ 25 ]. Altogether, these studies highlight that various accelerometer numbers and locations can be used to estimate vGRF.…”
Section: Introductionmentioning
confidence: 99%